Sleep Disturbances and Frailty Status in Older Community-Dwelling Men - Ensrud, Kristine E. (2009)
OBJECTIVES: Test the hypothesis that sleep disturbances are independently associated with greater evidence of frailty in older men. DESIGN: Cross-sectional analysis of prospective cohort study SETTING: Six U.S. centers PARTICIPANTS: 3133 men ≥67 years MEASUREMENTS: Self reported sleep parameters (questionnaire); objective parameters of sleep wake patterns (actigraphy data collected for an average of 5.2 nights); and objective parameters of sleep disordered breathing, nocturnal hypoxemia, and periodic leg movements with arousals (PLMA) (in-home overnight polysomnography). Frailty status classified as robust, intermediate stage or frail using criteria similar to those used in the Cardiovascular Health Study frailty index. RESULTS: The prevalence of sleep disturbances including poor sleep quality, excessive daytime sleepiness, short sleep duration, reduced sleep efficiency, prolonged sleep latency, sleep fragmentation (greater nighttime wakefulness and frequent long wake episodes), sleep disordered breathing, nocturnal hypoxemia and frequent PLMA was lowest among robust men, intermediate among men in the intermediate stage group, and highest among frail men (p-for-trend ≤0.002 for all sleep parameters). After adjusting for multiple potential confounders, self-reported poor sleep quality (Pittsburgh Sleep Quality Index <5, multivariable odds ratio (MOR) 1.28, 95%CI 1.09–1.50), sleep efficiency <70% (MOR 1.37, 95% CI 1.12–1.67), sleep latency ≥60 minutes (MOR 1.42, 95% CI 1.10–1.82), and sleep disordered breathing (respiratory disturbance index ≥15, MOR 1.38, 95% CI 1.15–1.65) were each independently associated with an increased odds of greater frailty status. CONCLUSION: Sleep disturbances including poor self-reported sleep quality, reduced sleep efficiency, prolonged sleep latency and sleep disordered breathing are independently associated with greater evidence of frailty.